Quality of life following surgery for congenital glaucoma: findings of the LVPEI congenital glaucoma registry - Gothwal, Vijaya K. (Eye (Lond), 2018)
PURPOSE: To evaluate the health-related quality of life (HRQoL) of children operated for primary congenital glaucoma (PCG) using the Kidscreen-27 questionnaire. METHODS: A total of 121 children (mean age, 11.8 years; SD, 2.8 years; 51% males) with unilateral or bilateral PCG who underwent glaucoma surgery in infancy (mean duration since surgery, 10.2 years; [SD] 4.2 years) by a single surgeon at a tertiary eye care centre were administered the Kidscreen-27 questionnaire (self-or interviewer administered in a face-to-face interview) during their routine follow-up visit. We investigated the measurement properties of Kidscreen-27 questionnaire using Rasch analysis and generated interval-level estimates of HRQoL. The main outcome measure was HRQoL (i.e., Rasch-derived Kidscreen score). Multivariable linear regression analyses assessed the influence of socio-demographic and clinical variables on the HRQoL of children with PCG. RESULTS: Majority (83%) of the children had bilateral PCG and congenital type of the disease (79%). Mean presenting acuity (logMAR) in the better eye was 0.32 (SD, 0.36; median, 0.18). Rasch analysis of Kidscreen-27 questionnaire indicated need for minor modifications following which a psychometrically robust unidimensional 23-item Kidscreen questionnaire emerged. In multivariable model, age of the child was independently associated with a 32% (β = −0.24 [95% CI, −0.11, −0.36]) increase in the HRQoL score. CONCLUSIONS: Despite undergoing successful glaucoma surgery, children with PCG reported reduced HRQoL. Younger children with PCG are more likely to experience this lowered HRQoL and ophthalmologists will need to be alert to this. Efforts must be made to improve the HRQoL of children with PCG.